Contract law - Andrews, Neil, barrister (Cambridge : Cambridge University Press, 2011)
'This textbook takes a fresh approach to contract law; as a first edition it reflects the subject in the 21st century more accurately than other texts. Comprehensive and scholarly, it maps the curriculum perfectly but detailed references and further reading sections encourage students to explore the subject further. Understanding is paramount and chapter introductions clearly guide students through the material. The textbook takes an innovative approach to case law: breaking down and discussing individual elements of a case and selecting short key extracts it gives students the tools to read cases independently and with confidence. An examination of the historical and theoretical foundations of the subject and a concluding chapter tracking emerging fields ensure the broadest possible perspective. Discussion of key recent cases such as Durham Tess Valley Airport (2010) and Chartbrook (2009) make this important new text a must for contract law students'--
'This textbook takes a fresh approach to contract law; as a fi rst edition it refl ects the subject in the 21st century more accurately than other texts. Comprehensive and scholarly, it maps the curriculum perfectly but detailed references and further reading sections encourage students to explore the subject further. Understanding is paramount and chapter introductions clearly guide students through the material. The textbook takes an innovative approach to case law: breaking down and discussing individual elements of a case and selecting short key extracts, it gives students the tools to read cases independently and with confi dence. An examination of the historical and theoretical foundations of the subject and a concluding chapter tracking emerging fi elds ensure the broadest possible perspective. Discussion of key recent cases such as Durham Tees Valley Airport (2010) and Chartbrook (2009) make this important new text a must for contract law students'--
Pt. I. Introduction -- Main features of contract law -- Pt. II. Formation -- The pre-contractual phase -- Offer and acceptance -- Certainty -- Pt. III. Consideration and intent to create legal relations -- Consideration and estoppel -- Intent to create legal relations -- Pt. IV. Third Parties and assignment -- Third parties -- Assignment -- Pt. V. Vitiating elements -- Misrepresentation -- Mistake -- Duress, undue influence, and unconscionability -- Pt. VI. Terms and Interpretation -- Terms in general -- Implied terms -- Interpretation and rectification of written contracts -- Exclusion clauses -- Pt. VII. Breakdown and liability -- Frustration -- Breach and performance -- Pt. VIII. Remedies for Breach -- Judicial remedies for breach of contract -- Consensual remedies for breach of contract : liquidated damages and deposits -- Pt. IX. Illegality and Public Policy -- Illegality and public policy -- Pt. X. The future -- International and European'soft law' codes : lessons for English law?
Includes bibliographical references (p. 697-723) and index.
Keywords: Contracts -- United Kingdom